Meningkatkan Niat Pembelian pada Website PT Travelicious Indonesia - Hamdan, Hamdan (Bina Nusantara University, 2014)
Today, the use of technology in the world of business is no longer considered uncommon. Technology and Internet are rapidly growing, and thus a lot of companies are now starting to see promising business opportunities via the Internet. The objective of this research is to increase purchase intention on PT Travelicious Indonesia’s website (www.Travelicious.co.id) in order to make the company survive and ready to face the competition by increasing customer’s purchase intention. This research analyzed the effect of website quality and perceived quality on brand image and its impact on Purchase Intention at PT Travelicious Indonesia. The methodology of this research is Path Analysis. The result of the research reveals that there is a positive and significant influence between website quality and perceived quality towards brand image and its impact on purchase intention.